1989
DOI: 10.1111/j.1365-3091.1989.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural characteristics and genesis of the aeolian sediments in the Kuwaiti desert

Abstract: Several types of aeolian deposits have been recognized in Kuwait: (a) smooth sand sheets that resemble desert floor sand, (b) immobile sands that include rugged vegetated sand sheets and wadi fill deposits, and (c) mobile sands that form active sand sheets and sand dunes. Simple size frequency curves illustrate the genetic relationship between the various aeolian sediment types. The four size parameters, namely, mean size, sorting, skewness and kurtosis, were calculated. Scatter plot diagrams of sorting versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 11 publications
3
26
0
2
Order By: Relevance
“…Quartz percentages are similar to those found in the Libyan Desert, the Saudi Arabian Desert and the Kuwaiti Desert (Mizutani and Suwa, 1966;Anton, 1983;Khalaf, 1989). The average data plotted in a Qt-FtLt ternary diagram with the standard deviation polygons show that the San Luis Río Colorado and the El Pinacate desert dune sands have a wider dispersion towards the Qt and Lt poles (Figure 3).…”
Section: Modal Analysis Of the Desert Dune Sandssupporting
confidence: 51%
See 1 more Smart Citation
“…Quartz percentages are similar to those found in the Libyan Desert, the Saudi Arabian Desert and the Kuwaiti Desert (Mizutani and Suwa, 1966;Anton, 1983;Khalaf, 1989). The average data plotted in a Qt-FtLt ternary diagram with the standard deviation polygons show that the San Luis Río Colorado and the El Pinacate desert dune sands have a wider dispersion towards the Qt and Lt poles (Figure 3).…”
Section: Modal Analysis Of the Desert Dune Sandssupporting
confidence: 51%
“…It could also be due to the fact that the El Pinacate dune field is farther from the source, which allows for longer aeolian transport and better sorting of the sands. The unimodal character of the skewness and kurtosis values shows that the sands are produced by only one sediment source (Khalaf, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The variations in textural characteristics of dune type within the same dune field in Kuwait are studied by Khalaf (1989) and Al-Dousari and Pye (2005). It is well noted from these studies that variations in statistical parameters of the same dune type sediments across the dune field (taking in consideration the time factor) in Kuwait is limited.…”
Section: Barchanmentioning
confidence: 99%
“…The variations in textural characteristics of dunes in Kuwait are studied by Khalaf (1989), Khalaf et al (1995), Al-Enezi (2001), and Al-Dousari and Pye (2005). However, statistical parameter variations over the dune body of Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Grain size variations in coastal and desert dune sands have been widely used to infer transport and depositional mechanisms [9,10]. For example, size coarsening of the dune sands may be due to wind deflation of fine grains leaving behind the coarse fraction in the sands [11]. It has been also observed that moderately to poorly sorted dune sands occur with short transport from the source of sediments to the dune systems [12].…”
mentioning
confidence: 99%